PENERAPAN TOTAL PERFORMANCE SCORECARD (TPS) DALAM UPAYA MEMBANGUN KOMITMEN PEGAWAI DI ORGANISASI SEKTOR PUBLIK - Sulistiani, Dwi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Every organization has a goal to be achieved. Therefore, the vision, mission, and strategy are structured with the support of organizational structures, formulas and systems that must be implemented, in order not to be wasted. The amount of funds, the amount of time, energy and thoughts poured in the organization is also a matter of free if there is no commitment of all employees in implementing the structure and system of the organization. Building employee commitment is mandatory to implement and can be done with two main things: embed the values of the organization or company and align the organizational goals and objectives of the employee.The values of organization or company that must exist include integrity, professionalism, innovation, teamwork that can shape or change the behavior / culture of employees and become an organizational work culture. Implementation of these organizational values must be followed by several critical success factors. The most important thing is thealignment of the company's desire to achieve effectiveness and efficiency with the desires of individual employees in relation to their personal well-being in an effort to improveintegrated performance and as a result of continuous improvement, development and learning through the application of Total Performance Scorecard (TPS).This literature review aims to increase knowledge and insight in building employee commitment in an effort to achieve organizational goals, especially in the public sector.Additionally, it adds an understanding of how to improve employee relationships with companies or organizations actively because employees who show a high commitmenthave a desire to provide more energy and responsibility in supporting the welfare and success of the organization where they work.Keywords: organization goals, employee commitment, Integrity, Professionalism, Innovation, Teamwork, Total Performance Scorecard.